Holocene Lake-Level Change and Submerged Archaeological Site Potential of Rice Lake, Ontario - Sonnenburg, Elizabeth (My University, 2010)
Isostatic rebound and climatic changes throughout the Holocene have resulted in several periods of lowered water-levels in the Great Lakes watershed. The Early Holocene lowstand phase corresponds with the Paleoindian period in the Great Lakes Region (11,000-9000 YBP), and subsequent water-level rise has inundated Paleoindian archaeological sites. This research sought to reconstruct the water-level history of Rice Lake (located north of Lake Ontario) in order to identify areas of high potential for submerged prehistoric sites.
Over 750 line km of detailed geophysical data (single-beam bathymetry) and 16 sediment cores were collected over a 30 km2 area of Rice Lake. Sediment cores were visually logged and analyzed for particle size, microfossils and microdebitage. Water-level reconstructions accounting for sediment infill and isostatic rebound of the lake record a post Lake Iroquois (after 12 ka BP) Early Holocene lowstand (~10-12 m below present level (bpl)) (EH-1). At 10 ka BP, gradually rising water-levels and establishment of wetlands as indicated by thecamoebian assemblages coincide with a newly discovered Paleoindian occupation of the Mcintyre basin, where quartz microdebitage was found. Waterlevel continued to rise to almost 2 m bpi until 6.5 ka BP, when warmer and drier temperatures caused a sudden drop in water-levels as recorded by a pollen hiatus. After 4 ka BP, water-levels quickly recovered and stabilized as shown by rapid recovery of pre-hiatus thecamoebian biofacies and the establishment of wild rice stands.
The small number of known, well-preserved Great Lakes Paleoindian sites has limited analysis of Early Holocene population densities, migration patterns, cultural diffusion, or the chronology of settlement. The method of modelling water-level fluctuations and associated archaeological potential developed in this thesis represents a substantial advance in our understanding of Early Holocene archaeology in the Great Lakes. These methods will have broader application to exploration of submerged terrestrial landscapes elsewhere in the Great Lakes and will allow for future regional synthesis of archaeological site distribution and characteristics.
Keywords: Holocene Lake-Level; Archaeological; Rice Lake, Ontario; Isostatic rebound; climatic changes